Hubungan Sikap dan Pengetahuan Ibu Menyusui dengan Pemberian ASI Eksklusif pada Bayi 0-6 Bulan di Desa Gunung Paribuan Kab.Deli Serdang Tahun 2023 - Ellina Kristina Sihombing; Basaria Manurung (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Breast milk is the best food for babies which contains white blood cells, proteins and immune substances that are suitable for babies. Breast milk is very suitable for meeting the baby's needs in all respects, namely carbohydrates in the form of lactose, polyunsaturated fatty acids, lactalbumin protein which is easily digested, contains lots of vitamins and minerals, a calcium phosphate ratio of 2:1 which is an ideal condition for calcium absorption, and contains anti-infective substances. This research aims to determine the relationship between attitudes and knowledge of breastfeeding mothers and exclusive breastfeeding for babies 0-6 months in Gunung Paribuan Village, Deli Serdang Regency in 2023. This type of research is research using an analytical survey with a cross method approach. sectional. The population is all mothers who have babies 0-6 months in Gunung Paribuan Village, Deli Serdang Regency, totaling 61 people. The number of samples used was 61 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 61 respondents, there was a relationship between the attitude of breastfeeding mothers and exclusive breastfeeding for babies 0-6 months old, showing that the p value = 0.012 < 0.05. There is a relationship between Mother's Breastfeeding Knowledge and Exclusive Breastfeeding for Babies 0-6 Months, showing that the p value = 0.002 < 0.05. It is recommended for Health Workers to increase education regarding Exclusive Breastfeeding.